Management of Hirschsprung’s Disease: A Survey with Brazilian Pediatric Surgeons - Cesar Saul Quevedo Penaloza; Alana Carnevale Barreto; Erika Veruska Paiva Ortolan; Augusto Zani; Pedro Luiz Toledo de Arruda Lourenção (Children)
Background: Hirschsprung’s disease (HD) is a congenital malformation of the enteric nervous system clinically manifested by intestinal obstruction in the neonatal period or severe constipation in childhood. Several surveys on HD have been conducted to evaluate experiences in its management around the world. For the first time in Brazil, we analyze and report the management patterns of HD among pediatric surgeons in Brazil. Methods: A validated questionnaire was disseminated in print at the Congress of Pediatric Surgery in São Paulo-Brazil, and an online version was sent to all the active members of the Brazilian and Paulista Institute of Pediatric Surgery. Results: In total, 361 pediatric surgeons answered the survey. Of these, 329 completed all questions (response rate: 91%). Most Brazilian services treat fewer than 10 cases of HD annually. The preferred diagnostic method was rectal biopsy. For newborns (NBs) and infants, open biopsy was the most commonly used technique. For NBs with HD clinically stable 50% of specialists chose immediate surgery. In NBs and infants with classic HD, the Soave technique (69%) is the most common surgical intervention, and the transanal route (80%) is the preferred surgical approach. In children over 3 years of age with classic HD, the most-used technique is the Duhamel method (54%), with the open approach being the most common (52%). Conclusions: Our study in Brazil found that HD patient management aligns with scientific evidence and international guidelines.